Clinical and laboratorial features of spontaneous bacterial peritonitis in southern Brazil - Thiele, Gabriela Bicca; Silva, Otávio Marcos da; Fayad, Leonardo; Lazzarotto, César; Ferreira, Mariana do Amaral; Marconcini, Maíra Luciana; Dantas-Corrêa, Esther Buzaglo; Schiavon, Leonardo de Lucca; Narciso-Schiavon, Janaína Luz (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Spontaneous bacterial peritonitis (SBP) is a severe complication that occurs in 8-27% of hospitalized patients with liver cirrhosis and ascites, with high mortality rates. This study aimed to identify the clinical characteristics associated with SBP. DESIGN AND SETTING: Cross-sectional study, conducted in a public university. METHODS: The study consecutively included individuals with liver cirrhosis and ascites between September 2009 and March 2012. Forty-five patients were included: mean age 53.2 ± 12.3 years, 82.2% male, 73.8% Caucasian, mean Model of End-stage Liver Disease (MELD) score of 19.5 ± 7.2, and 33.3% with SBP. The subjects were divided into two groups: SBP and controls. RESULTS: Comparison between individuals with SBP and controls showed that those with SBP had lower mean prothrombin activity time (36.1 ± 16.0% versus 47.1 ± 17.2%; P = 0.044) and lower median serum-ascites albumin gradient (SAAG) (1.2 versus 1.7, P = 0.045). There was a tendency towards higher mean MELD in the SBP group, not significant (22.2 ± 7.6 versus 17.9 ± 6.7; P = 0.067). There was a strong positive correlation between the neutrophil count in ascitic fluid and serum leukocyte count (r = 0.501; P = 0.001) and a negative correlation between the neutrophil count in ascitic fluid with prothrombin activity time (r = -0.385; P = 0.011). CONCLUSION: A few characteristics are associated with the presence of SBP, especially liver dysfunction, SAAG and peripheral leukocytosis.